EVALUASI PELAKSANAAN PROGRAM PENANGGULANGAN TUBERKULOSIS PARU (P2TB) DI PUSKESMAS BANDARHARJO KOTA SEMARANG - Farida Arisalah Putri; Chriswardani Suryawati; Wulan Kusumastuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
ABSTRACTBackground: The TB situation in Indonesia is getting worse because the number of TB cases continues to increase and is increasing. In response to this, it is necessary to do again related to TB control in order to increase cure rates and reduce mortality. Objective: To evaluate the implementation of the TB control program at the Bandarharjo Health Center. Method: This study uses qualitative and analytic descriptive methods through in-depth interviews which are selected based on purposive sampling techniques. Results: Input Components: enough Human resources, Lack of training, existing P2TB purgatory, low funding, good facilities and infrastructure, SOP of applicable regulations and ISTC. Process components: No specific planning documents, no specific and written organizational structure, internal and external coordination is good, the implementation of activities is good, there is no optimal yet, recording and reporting is good, monitoring is Less questionable. Output component: Case finding and treatment n success rates do not meet national TB targets. Conclusion: The input component is good, the process component there are still some activities that are not optimal, the output component has not met the national TB targets in the TB control program at The Bandarharjo Health Center. Keywords: Evaluation, TB control, P2TB, Bandarharjo Health Center.